Genetic Conservation Management of Marine Resources and Ecosystems of Patagonian Fjords - Addamo, Anna Maria; Zaccara, Serena; Försterra, Günter; Höfer, Juan; García-Jiménez, Ricardo; Crosa, Giuseppe; Machordom, Annie (Frontiers in Marine Science, 2021)
The Chilean fjord region includes many remote and poorly known areas where management plans for the marine living resources and conservation strategies are urgently needed. Few data are available about the spatial distribution of its marine invertebrate fauna, prevalently influenced by complex interactions between biotic and abiotic factors, animal behavior and human activities. Patagonian fjords are a hotspot for finfish aquaculture, elevating Chile to the world’s second producer of farmed salmon, after Norway, a condition that emphasizes the necessity to develop strategies for a sustainable aquaculture management. The present study focuses on the emblematic cold-water coral Desmophyllum dianthus, dwelling the Comau Fjord from shallow to deep waters, with the aim to illustrate population structure, demography and adaptation of the species and its potential use for the development of a sustainable conservation and management plan for human activities. The analyses of microsatellite loci of D. dianthus individuals from four sampling localities along horizontal and vertical gradients of Comau Fjord, lead to identify them as a panmictic population. The results also contributed to consider a careful examination of the synchrony between the temporal and spatial variations of environmental factors and the biological cycle of the species as key role player in the inference of autecology of the species. The discussion stresses the importance of molecular analyses as extremely helpful tools for studies focusing on remote areas and non-model organisms, where logistic difficulties and limited scientific knowledge hamper a better management and conservation of marine resources, and in particular the relevance of multidisciplinary approaches to reduce the extensive knowledge gap on the remote fjord ecosystems of Patagonia. This study also highlights the importance of oceanographic information in the entire process of the analyses and interpretation of genetic results.